Joint inversion of magnetotelluric and seismological observations: case study in NE Brazil - Romero, Ana Milena Nemocón (2023)
Geophysical methods aim at obtaining information about the subsurface rocks and fluids. To achieve this goal, different methodologies are employed to more accurately determine both the geometry and physical properties of the Earth’s strata at depth. Seismological methods recover structural and velocity information in the subsurface, while MT techniques are powerful tools to characterize the saturation of fluids, such as hydrocarbons or saline water, in subsurface rocks. Seismological or magnetotelluric (MT) measurements provide incomplete information when used independently. Combined, these techniques have the potential to considerably improve the imaging of structural features at depth. This paper evaluates the performance of joint analysis of seismological and magnetotelluric data for determination of subsurface structure beneath the Borborema Province and northern São Francisco Craton, using data collected along a N-S profile centered at the Araripe Basin. First, resistivity and S-wave velocity models were obtained through independent inversions. The velocity models were obtained through simultaneous inversion of receiver functions and dispersion curves, and revealed the presence of a layer with high velocity (4.1-4.3 km/s) below the Araripe Basin - which was interpreted as a mafic layer in the lower crust - and a decrease in velocity (< 4.3 km/s) below 120 km depth. The resistivity models were taken from an existing 3D inversion of apparent resistivity and phase curves, noting the presence of high conductivity ( 25 Ωm ) in the mantle (120 km) beneath the basin. This conductive anomaly was interpreted as material enriched with small amounts of magma derived from Mesozoic rifting processes. The joint interpretation of the results thus evidences a thinning of the lithosphere beneath the Araripe Basin, contributing to improve our understanding of the tectonic inversion processes of this basin. The performance of the joint inversion of magnetotelluric and seismological data was also investigated. The joint inversion used the same receiver functions, phase and apparent resistivity curves as the independent inversions; however, a brand-new mean phasevelocity dispersion curve had to be utilized. The inversion assumes a common seismic and resistivity structure (1D), represented by a set of layers above a half-space. Furthermore, the inversion is performed using a multi-objective genetic algorithm (GA) that efficiently exploits the parameter space. Our results demonstrate that, in spite of considerable geological complexity, it is possible to determine structurally consistent velocity and resistivity structures beneath the Borborema Province and the São Francisco Craton. The inverse (1D) models do not allowed to develop empirical relationships between resistivity and S-wave seismic velocity at crustal or mantle depths, but they were able to image an electric Moho beneath most locations within the study region.